Development of Fiqh E-Modules Based on Contextual Approach for Class X Students of Ma Muhammadiyah 2 Malang - Anggi Hidayat, Mohammad; Hady, M. Samsul; Susilawati, Samsul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to develop a contextual approach-based Fiqh E-Module and test its effectiveness in improving student learning outcomes. The research uses the Research and Development (R&D) method which includes the stages of validation by material and media experts, module improvement based on validator suggestions, and implementation through trials using a Quasi Experimental design with Nonequivalent Control Group Design. The research sample consisted of 29 grade X students at MA Muhammadiyah 2 Malang, which were divided into experimental and control classes. The validation results showed that the module was considered very feasible with a percentage of 92% from the material aspect and 88% from the media aspect. The pilot test showed a significant increase in student learning outcomes in the experimental class, which used the E-Module, compared to the control class that followed learning without the module. The average post-test score of the experimental class was 93.29, much higher than the control class with an average of 48.35. The results of the user response questionnaire show that students are very enthusiastic and feel helped by the use of modules in the learning process. In conclusion, the developed E-Module effectively improves student learning outcomes and is suitable for use as learning media.